Evaluating the effect of stress management programmes at the work-site on absenteeism reduction: a systematic review (Italian Journal of Public Health, 2006)
Background: In the European Union, work-related stress affects about one in four workers, and it may beresponsible for the loss of productivity, healthcare consumption and absenteeism. The objective of our studywas to estimate whether stress programmes aimed at managing and preventing work-related stress reducedthe rate of absenteeism.Methods: We searched electronic databases for relevant articles assisted by hand searching for references.We included studies that had an experimental or quasi-experimental design, describing an interventionfocused either on the work organisation or on workers’ characteristics as well as reporting a measure ofabsenteeism.Results: The search identified 2520 articles: among these, nine met our inclusion criteria. Stressmanagement programmes reduced absenteeism shortly after the intervention however in the long termthere was no evidence to support this.Conclusion: Future studies should evaluate stress management programmes that consist of repeatedinterventions over longer periods of time, focusing on effectiveness and relative costs.
Keywords: work-related stress; stress management programmes; absenteeism; systematic review